New Leucettidae de Laubenfels, 1936 (Porifera, Calcarea) from Western Australia - Leocorny, Pedro; Alencar, Aline; Fromont, Jane; Klautau, Michelle (Zootaxa, 2016)
This paper reports four new Leucettidae (Porifera, Calcarea) from Western Australia, with two representatives of Leucetta and two of Pericharax: L. foliata sp. nov., L. purpurea sp. nov., Pericharax crypta sp. nov., and P. vallii sp. nov. This is the first time tripods have been described within Pericharax. In addition, one species (L. foliata sp. nov.) has an external morphology not previously reported for Leucetta, and for the first time tetractines of the inhalant and exhalant canals have been distinguished. Leucettidae now comprises 28 species, eight of them occur in Western Australia, which means this Australian State has the highest species richness for this family in Australia. The WA coastline has been largely unexplored for Calcarea so it is likely that further collecting will yield additional species. Leucetta microraphis is the most widespread species of Leucettidae in Australia, occurring in all States except the Northern Territory and Tasmania. We highlight the importance of a revision of the Leucettidae using molecular and morphological characters to determine which morphological characters have a phylogenetic signal.